Is Asthma Associated with Increased Risk of Injury? - Liang, Wenbin; Chikritzhs, Tanya; Lee, Andy (Marcel Dekker, 2011)
Background. Asthmatic patients are at higher risk of fracture and bruising due to the systemic side effects of corticosteroid medication. However, the link between asthma and injury leading to these adverse outcomes remains unclear. Objective. This study investigated asthma and cause- and type-specific injury at the population level. Methods. Using data from the 2001 and 2004 Australian National Health surveys (n = 52,768), the prevalence and risk of experiencing specific causes and types of injury in the past 4 weeks were assessed by logistic and Poisson regression analyses. Results. A history of asthma was associated with a higher prevalence of injury for both adults and children, as well as increased risk of incurring various causes and types of injury, after accounting for the effects of confounding factors. Conclusions. The associations cannot be explained by the physiological systemic side effects of medication alone. Further research is needed to understand the underlying relationship so that an appropriate injury prevention strategy can be developed for asthma sufferers.